“Judge-Only” Justice V. Collaborators: Introduction - Maria Cristina Reale (Oñati Socio-Legal Series)
Who and how many are the collaborators of judges? The answer may differ according to the perspective under which Justice is considered. In this introduction, and in the light of the papers submitted in the first session of the workshop, a distinction is proposed between “direct” and “indirect” collaborators of judges, according to the side of Justice observed. If Justice is confined simply to the classical function performed by courts, i.e. deciding cases according to the law, it seems quite obvious to remark that judges never act alone, since they normally benefit from the help of different kinds of assistants who, at different levels, help them in their daily work. But when paying attention to the facet of Justice concerning the concrete enforcement of decision, it becomes inevitable to take into account different categories of subjects involved in the “administration” of justice. Under this second perspective, justice is a matter for everyone: not only judges and prosecutors, but other professionals and bodies, including also Governments and other public institutions, since their decisions concerning, for example, human and material resources assigned to the judicial system have inevitably an impact on Justice considered as a public service. Lastly, the aptitude of the public opinion cannot be ignored: the degree of public satisfaction with the judicial system may influence the demand of justice as well as its material functioning. Accordingly, even common citizens could be seen as a very peculiar sort of “collaborators” of judges.